Modeling Academic Self Efficacy and Social Support to Increase Academic Engagement of Health Student Through Academic Resilience as an Intervening - Kiftiyah Kiftiyah; Ika Andrini Farida; Bambang Budi Wiyono; Imanuel Hitipeuw (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2024)
Academic engagement is currently an important focus in education. This is because the academic engagement that students have will have a significant impact on the abilities of nursing students, especially in providing nursing care and services. Some of the impacts of students' lack of academic engagement result in students experiencing decreased learning achievement and not being active in learning activities in class. The aim of this research is to analyze the influence of self-efficacy and social support on nursing students' academic engagement through academic resilience as an intervening variable. This research is research development. This research was conducted in the Mojokerto Regency area. The sample in this study was 590 nursing students from health institutions in Mojokerto Regency who were determined using stratified random sampling. The variables in this research are self-efficacy, social support, academic resilience and academic engagement. Data analysis was carried out using confirmatory factor analysis. The results of the research show that self-efficacy and social support contribute significantly to academic engagement, academic resilience has a significant effect on academic engagement, and self-efficacy and social support contribute significantly to academic engagement through academic resilience. The high academic engagement that health students have during their education will help students to be actively involved in academic and non-academic activities. One effort to increase students' academic engagement is to stimulate self-efficacy and social support while students are studying education